La documentation historique comme effet de vérité dans le roman contemporain - Epp, Marla (My University, 2018)
This article examines the citation of historical documents in Les Onze and HHhH, two novels inspired by archival materials, with a first-person narrator who styles himself as a historical expert. The citing of documents should, according to historians, be a mark of the text’s reliability, although in these novels it does not always provoke the desired result. Their respective appropriation of a historical style of writing plays with the reader’s expectations and provokes interrogations as to how best to represent history.
Keywords: citation; historical documents